Preparation and damping properties of (waste rubber powder)/hindered phenol composites. Issue 4 (27th May 2014) - Li, Mingjun; Zhu, Wenhong; Xu, Yongwen; Fu, Maosheng; Cao, Yihua
<x xml:space="preserve">Abstract</x> Waste rubber powder (WRP)/hindered phenol composites were successfully prepared by mixing tetrakis[methylene‐3‐(3‐5‐ditert‐butyl‐4‐hydroxy phenyl) propionyloxy] methane (AO‐60) into WRP for modification and recycling. The damping properties of the composites were systematically investigated through dynamic mechanical analysis. The experimental results indicate that the damping loss factor (tan δ) of WRP increases sharply from 0.366 to 0.734 via the modification process. With an increase in AO‐60, the tan δ value and the storage modulus in the glassy state gradually increase, and temperature dependence of loss peak gradually improves. The effects of the particle size of WRP, vulcanization temperature, vulcanization pressure, and vulcanization time on damping properties of the composite were investigated further. J. VINYL ADDIT. TECHNOL., 20:225–229, 2014. © 2014 Society of Plastics Engineers